Evaluation of outcomes in 201 child and youth survivors of Child Sexual Abuse (CSA) who participated in a one-year multimodal treatment program - Matthew Reeson; Hannah Pazderka; Wanda Polzin-Homan; Yifeng Wei; Andrew Greenshaw; Peter H. Silverstone (PLoS ONE, 2026)
Background and rationale Child sexual abuse (CSA) is a pervasive and prevalent form of early-life trauma that can increase the risk for PTSD, mood disorders, substance abuse, harmful behaviour, non-suicidal self-harm, suicidal ideation, and death by suicide. Preliminary research has shown positive impacts of multimodal treatment for youth survivors of CSA, but no ‘gold-standard’ currently exists for CSA treatment. The aim of this study was to provide a secondary analysis of data from a longitudinal, episodic, and multimodal treatment program specifically designed to treat child and adolescent survivors of CSA. Methods Child and youth survivors of CSA aged 8–17 completed a one-year multimodal treatment program at a dedicated facility known as the Little Warriors Be Brave Ranch. Participants completed self-report outcome measures for PTSD, depression, anxiety, self-esteem, quality of life, family functioning, and substance use at intake and graduation from the program. Changes in reported outcomes for child and youth participants were analyzed over the course of treatment. Results A total of 201 sequential individuals who completed the one-year treatment program between January 2022-January 2026, from an initial group of 253 participants, were included in this analysis. Most of the completers were biologically female (n = 166, 82.6%) and were adolescents aged 13–17 (n = 116), while the remainder were children aged 8–12 (n = 85). Overall, positive changes in all outcomes were reported in participants from both groups. The largest effect was reported in adolescent PTSD symptoms (d = 0.94, p < 0.001), depression (d = 0.88, p < 0.001), and anxiety (d = 0.86, p < 0.001). Large effect sizes were also reported in levels of PTSD (d = 0.72, p < 0.001), depression (d = 0.82, p < 0.001), and anxiety (d = 0.64, p < 0.001) in child participants. Participants whose PTSD scores remained above the clinical threshold at graduation had higher levels of family dysfunction, more complex histories of trauma, and lower resilience scores. Conclusion The findings of this study support the use of a multimodal treatment program for youth CSA survivors. The results suggest that this program design has the capacity to benefit CSA survivors across several domains of mental health and well-being. However, the findings of this study are limited by the lack of a control group. Future research should investigate the long-term effects of treatment, and include comparisons to a control sample, to further elucidate the sustainability of these positive therapeutic outcomes.